A Note on Taylor-Eddy and Kovasznay Solutions of NS-α-Deconvolution and Leray-α-Deconvolution Models. (20th January 2014) - Rebholz, Leo G.; Watro, Stacey A.
Abstract : We show that both the Taylor-eddy and Kovasznay exact solutions of the Navier-Stokes equations are also exact solutions of both the NS- α -deconvolution and Leray- α -deconvolution models, but with modified pressures that converge to the Navier-Stokes pressure solution asα → 0 or the order of deconvolution tends to infinity. The existence of these exact model solutions will provide for better benchmark testing and validation of numerical codes and also shows that the models preserve these special structures.